THE MOTIVATIONS OF CONNIE’S ADULTERY WITH MELLORS IN THE NOVEL LADY CHATTERLEY’S LOVER - Mukhlasul Fasikh (Journal of English Language and Literature (JELL), 2017)
This objective of this research is to add to the students’ knowledge of the Connie’s motivation in committing adultery. In addition, the objectives are to find out the character of Connie, to give evidence and find out the motivation of Connie’s adultery with Mellors then to know the reaction of Clifford to students, teachers and people who want to analyze the Connie’s motivation in committing adultery. This research is a library research. The research was done through reading the novel and other sources related to the motivation of Connie’s adultery. The data was taken from books, dictionary, and internet. The researcher uses qualitative method to analyze the motivation of Connie in committing adultery. The novel tells about Connie as the female protagonist of the novel. At 23, she marries Clifford Chatterley. After a month’s honeymoon, Clifford is sent to war, and returns paralyzed from the waist down and become impotent. After that, he becomes a successful writer. Into the void of Connie's life comes Oliver Mellors, the gamekeeper on Clifford's estate. Connie feels curiously drawn to him. After several meetings him, they meet by chance at a hut in the forest. And they have sex more than twice. This time, Connie begins to adore Mellors. She is proud to believe that she is bearing Mellors’ child. Adultery means he or she physically engages in sexual acts with someone who is not his or her spouse. They commit adultery due to several motivations such as the weaknesses of their partner, chances to meet their paramour that grow them in love. Understanding of the people’s motivation in committing adultery is very important before judging them unpleasantly